Challenges and opportunities at the nexus of energy, water, and food: A perspective from the southwest United States. (17th April 2018) - Armstrong, Neal R.; Shallcross, R. Clayton; Ogden, Kimberly; Snyder, Shane; Achilli, Andrea; Armstrong, Erin L.
ABSTRACT: Abstract : Large regions of the United States (and the world) face "situational scarcities" of water that arises from energy extraction and use, agricultural practices, expanding urban populations, and poorly integrated water policies. Creating "fit-for-purpose" water from suboptimal sources will require new materials and a new understanding of the separation of contaminants from complex aqueous media. We review here scientific, technological, and societal challenges at the nexus of energy, water, and food. We focus on specific examples of energy and water stress in the southwestern United States and technological routes to new sources of water. Situational scarcities of water are increasing worldwide because of the reliance on uncertain water sources, coupled with expanding populations, expanded agricultural uses of water, and water and energy use policies that have not always been effectively integrated. This review is framed using the outcomes of recent National Science Foundation workshops focusing on the Energy/Water/Food Nexus and from other recent U.S. Department of Energy workshops focused on the Energy/Water nexus. Water-stressed regions, even after extensive conservation measures, may need new supplies of water that come from less than optimal sources. A basic understanding of the separation of water from complex aqueous solutions along with new materials, distributed and publically accepted technologies and unit operations, underpin the future production of "fit-for-purpose" water. Regional test beds are required that are small and provide for simultaneous control of a number of variables, yet large enough to approximate real communities. Solutions to these problems represent opportunities for innovation and creation of economically viable, resilient communities.